Overweight and menstrual disorders in girls aged 12-15 years - Purba, Siska Octaviani; Arto, Karina Sugih; Saragih, Rina Amalia C. (Paediatrica Indonesiana, 2023)
Background Several studies have noted a strong association between fat distribution and menstrual disorders. Many studies have evaluated the association between nutritional status and menstrual disorders, but the results remain inconclusive. Objective To assess for possible associations between overweight and menstrual disorders in girls aged 12-15 years. Methods A cross-sectional study was conducted in girls aged 12-15 years who had undergone menarche. Nutritional status was classified based on the Centers for Disease Control and Prevention curve for body mass index (BMI) as overweight (P85-P95) and normal weight (P3-<P85); those underweight (<P3) were excluded. We recorded the subjects’ BMI, waist circumference (WC), waist circumference-to-height ratio (WtHR), menstrual pain (using the visual analog scale), menstrual cycle length, menstrual period duration, and bleeding volume (estimated by the daily number of menstrual pads used) and compared these variables between normal weight and overweight subjects. Results Of 73 subjects, 32.9% were overweight and 67.1% had normal weight. There were significant associations between overweight and menstrual disorders (prevalence ratio, PR=1.304; P=0.027), irregular menstrual cycle (PR=4.696; P<0.001), abnormal menstrual period duration (PR=2.45; P<0.001), and excessive bleeding volume (PR=9.528; P<0.001). No significant association was found between overweight and menstrual pain (P=0.227). BMI, WC, and WtHR were significantly higher in girls with irregularity and abnormal duration of menstrual cycles, but not in girls with excessive menstrual pain. Conclusion Overweight is significantly associated with menstrual disorders, irregular menstrual cycle, abnormal menstrual period duration, and abnormal volume of menstrual loss, but not with menstrual pain.